2014
DOI: 10.1088/0004-637x/790/1/8
|View full text |Cite
|
Sign up to set email alerts
|

An Unorthodox X-Class Long-Duration Confined Flare

Abstract: We report the observation of an X-class long-duration flare which is clearly confined. It appears as a compactloop flare in the traditional EUV passbands (171 and 195 Å), but in the passbands sensitive to flare plasmas (94 and 131 Å), it exhibits a cusp-shaped structure above an arcade of loops like other long-duration events. Inspecting images in a running difference approach, we find that the seemingly diffuse, quasi-static cusp-shaped structure consists of multiple nested loops that repeatedly rise upward a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 53 publications
(62 reference statements)
10
59
2
1
Order By: Relevance
“…Nevertheless, distinctive discrepancies between QSLs footprints and flare ribbons can also be found in NLFFF extrapolations. Indeed, this clearly appears in the atypical flare studied by Liu et al (2014), as can be seen in their Figs. 7d and e. We thus conjecture that such mismatches between QSLs footprints and flare ribbons are more generally inherent to the force-free model of choice.…”
Section: Qsls and Flare-ribbonsmentioning
confidence: 63%
“…Nevertheless, distinctive discrepancies between QSLs footprints and flare ribbons can also be found in NLFFF extrapolations. Indeed, this clearly appears in the atypical flare studied by Liu et al (2014), as can be seen in their Figs. 7d and e. We thus conjecture that such mismatches between QSLs footprints and flare ribbons are more generally inherent to the force-free model of choice.…”
Section: Qsls and Flare-ribbonsmentioning
confidence: 63%
“…These properties also usually point to the standard flare model of an eruptive flare, with reconnection continuing to extract energy from the field and cause the formation of the arcade of flare loops. In this case, Liu et al (2014) suggested that new emergence of magnetic field in the region of the second arcade triggered the events.…”
Section: Flares Cmes and X-class Flares Without Cmesmentioning
confidence: 86%
“…In this picture, the photospheric traces of the HFT are 2J-shaped (Titov 2007;Aulanier et al 2010) and they match the 2J-shaped flare ribbons of classical two-ribbon flares (Chandra et al 2009;Schrijver et al 2011). The match between the shapes of QSLs and flare ribbons has been achieved recently by Liu et al (2014), Savcheva et al (2015), and Zhao et al (2016). These QSLs have been shown to move together with the flare ribbons in direction perpendicular to the polarity inversion line (PIL) (Savcheva et al 2016b;Janvier et al 2016).…”
Section: Introductionmentioning
confidence: 84%